The Rationale, Feasibility, and Optimal Training of the Non-Physician Medical Nutrition Scientist. (9th August 2015) - Ettinger, Susan E.; Nasser, Jennifer A.; Engelson, Ellen S.; Albu, Jeanine B.; Hashim, Sami; Pi-Sunyer, F. Xavier
Abstract : Dietary components have potential to arrest or modify chronic disease processes including obesity, cancer, and comorbidities. However, clinical research to translate mechanistic nutrition data into clinical interventions is needed. We have developed a one-year transitional postdoctoral curriculum to prepare nutrition scientists in the language and practice of medicine and in clinical research methodology before undertaking independent research. Candidates with an earned doctorate in nutrition science receive intensive, didactic training at the interface of nutrition and medicine, participate in supervised medical observerships, and join ongoing clinical research. To date, we have trained four postdoctoral fellows. Formative evaluation revealed several learning barriers to this training, including deficits in prior medical science knowledge and diverse perceptions of the role of the translational nutrition scientist. Several innovative techniques to address these barriers are discussed. We propose the fact that this "train the trainer" approach has potential to create a new translational nutrition researcher competent to identify clinical problems, collaborate with clinicians and researchers, and incorporate nutrition science across disciplines from "bench to bedside." We also expect the translational nutrition scientist to serve as an expert resource to the medical team in use of nutrition as adjuvant therapy for the prevention and management of chronic disease.